Bioecological and Molecular Studies of Heliothis nubigera Herrich-Schäffer, 1851 and Trichoplusia ni (Hübner, [1803]) associated with Ferula communis L. as a new host in AlUla, Saudi Arabia (Lepidoptera: Noctuidae) - Rayan M. Alansari; Amin A. Seleem (SHILAP, 2024)
Heliothis nubigera Herrich-Schäffer, 1851 and Trichoplusia ni (Hübner, [1803]) (Lepidoptera: Noctuidae) are serious polyphagous for economic crops searching for a host to complete their life cycle. The present study was conducted to estimate the relationship between Heliothis nubigera and Trichoplusia ni with Ferula communis L. in two locations, Hassat Al-dab and Almotadal, AlUla Government, Almadina Almunawarah, Saudi Arabia. Genomic DNA was isolated from Heliothis nubigera and Trichoplusia ni for molecular identification. The results indicate that Heliothis nubigera and Trichoplusia ni completes their larval stages during the growth of Ferula communis. Molecular identification by gene sequencing of the target fragment of COI showed 100% identical to Heliothis nubigera with Accession number HM875008.1 and 98.44% identical to Trichoplusia ni with Accession number KX862907.1 using BLAST/N. The study concludes that the target fragment of the COI mitochondrial gene is a useful method for the identification of Heliothis nubigera and Trichoplusia ni. The study recorded that Heliothis nubigera and Trichoplusia ni use Ferula communis as a new host plant located in Hassat Al-dab and Almotadal, AlUla Government, Saudi Arabia.